Trans-Reactivation: A New Epigenetic Phenomenon Underlying Transcriptional Reactivation of Silenced Genes. - Maria Cristina Onorati (PLoS Genetics, 2015)
In order to study the role played by cellular RNA pools produced by homologous genomic loci in defining the transcriptional state of a silenced gene, we tested the effect of non-functional alleles of the white gene in the presence of a functional copy of white, silenced by heterochromatin. We found that non-functional alleles of white, unable to produce a coding transcript, could reactivate in trans the expression of a wild type copy of the same gene silenced by heterochromatin. This new epigenetic phenomenon of transcriptional trans-reactivation is heritable, relies on the presence of homologous RNA's and is affected by mutations in genes involved in post-transcriptional gene silencing. Our data suggest a general new unexpected level of gene expression control mediated by homologous RNA molecules in the context of heterochromatic genes.